Peta Falsafat Islam di Indonesia - Aan Rukmana; Sahrul Mauludi (ILMU USHULUDDIN, 2014)
This research is very important to understand the discourses of Islamic philosophy in Indonesia. The responses of the people to this theme are greatly varied. This article tries to discuss the response of Muslims towards Islamic philosophy. Some accept Islamic philosophy and try to develop it but others reject it. The debate between al-Ghazālī and Ibn Rushd is widely influencing the acceptance of the Muslims toward philosophy. Harun Nasution, Nurcholish Madjid, and Mulyadhi Kartanegara are the important figures in promoting Islamic philosophy in Indonesia.